1987
DOI: 10.1021/bi00398a007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of 2-acetylthiamin pyrophosphate: an enzymatic reaction intermediate

Abstract: The synthesis of 2-acetylthiamin pyrophosphate (acetyl-TPP) is described. The synthesis of this compound is accomplished at 23 degrees C by the oxidation of 2-(1-hydroxyethyl)thiamin pyrophosphate using aqueous chromic acid as the oxidizing agent under conditions where Cr(III) coordination to the pyrophosphoryl moiety and hydrolysis of both the pyrophosphate and acetyl moieties were prevented. Although the chemical properties exhibited by acetyl-TPP are similar to those of the 2-acetyl-3,4-dimethylthiazolium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…17 Its lowest energy absorption band in acetonitrile (λ max = 316 nm, ε M = 7,150 M −1 cm −1 ) was fully within expectations. Addition of trifluoroacetic acid (TFA) allowed measurement of the transient protonated species, blue-shifted in accord with the literature (λ max = 312 nm), 12,15 before rapid conversion to the TFA addition product 12.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…17 Its lowest energy absorption band in acetonitrile (λ max = 316 nm, ε M = 7,150 M −1 cm −1 ) was fully within expectations. Addition of trifluoroacetic acid (TFA) allowed measurement of the transient protonated species, blue-shifted in accord with the literature (λ max = 312 nm), 12,15 before rapid conversion to the TFA addition product 12.…”
supporting
confidence: 66%
“…A careful study by Gruys et al of a related system, acetyl-ThDP (18, Scheme 2) showed that, while imine formation could not be detected, cyclization to the carbinolamine (19, Scheme 2) was clearly evident. 12 To examine the UV-spectroscopic behavior of such a possible conjugated π-system, a second model, N-(1-(4-methylthiazol-2-yl)allylidene)benzenamine (17, Scheme 2) was constructed. Once again 4-methylthiazole (9) Charge-transfer (CT) phenomena are often invoked to explain bathochromic shifts seen in protein chromophores, and, indeed, they have been proposed for other ThDP-dependent enzymes.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The net rate constant of the phosphorolytic cleavage of AcThDP (k′ 6 3 , and k′ 4 ). Because all of these rate constants have been already determined, the calculation of k′ 6 is straightforward.…”
Section: Chemicals Andmentioning
confidence: 99%
“…It should be noted that AcThDP is in equilibrium with its internal hydrate and a carbinolamine form under the chosen conditions (3) and that all three species occur in comparable fractions. It is therefore challenging to observe AcThDP in only small amounts being present at steady state because the analytical signal splits off further.…”
Section: Chemicals Andmentioning
confidence: 99%